Application of 4 birthweight curves and local reference range at a University Hospital of Rio de Janeiro, BrazilAJOG Global Reports at a Glance - Fabio G. Da Matta, MD, MSc; Karina Bilda de Castro Rezende, MD, PhD; Maria Isabel M.P. Cardoso, MD, MSc; Luiza P. Ladeira, MD; Rita G. Bornia, MD, PhD; Joffre Amim, Jr., MD, PhD (AJOG Global Reports, 2024)
BACKGROUND: Numerous fetal growth curves have been developed from various subpopulations and geographic locations worldwide. OBJECTIVE: To determine the birthweight standard at the Maternity School and compare it to currently used standards in the clinical practice services. STUDY DESIGN: Cross-sectional, observational, and descriptive study. Data from infants born between 2011 and 2016 were collected from the Maternity School Hospital of the Federal University of Rio de Janeiro to define the 10th, 25th, 50th, 75th, and 90th percentiles of the birthweight by gestational age. It was determined the performance of the INTERGROWTH-21st, Fenton, Alexander, and Lubchenco for the Maternity School standards. RESULTS: After the 33rd week of pregnancy, the INTERGROWTH standard was similar to the local standard for small-for-gestational-age infants and Fenton for large-for-gestational-age infants at Maternity School Hospital. The INTERGROWTH standard was found to be inadequate to classify small-for-gestational-age infants, which are babies at major risk for morbidity and mortality at the onset of the 33rd week of pregnancy. CONCLUSION: It was possible to define reference values for birthweight for the maternal school hospital considering at least 33 weeks of pregnancy with a 95% confidence interval. The comparison of the INTERGROWTH, Fenton, Alexander, and Lubchenko standards to the maternal school hospital curve showed that the Fenton curve was the most suitable for the diagnosis of small for gestational age.